Rancang Bangun Media Pembelajaran Augmented Reality Mengenal Alat Musik Degung - Yunita Agustin Mulyana; Iwan Rizal Setiawan; Lelah Lelah (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Augmented Reality is one of information technology that still exists and being developed till now. This technology can show up a not real object in the real background. As we know, we can use technology to help our work and help us to make everything simple and easier. Nowadays, everything got easier and easier to do because of technology, it’s because a lot of people try to make something useful to help them with their work. Therefore, this study uses one of the technologies, augmented reality, to introduce traditional musical instruments named Degung to all people who want to know about this instrument. They who want to show Degung to other but do not know an easy way, can use the result of this study using MDLC (multimedia development life cyle) method.